Klasterisasi Mahasiswa Difabel Indonesia Berdasarkan Background Histories dan Studying Performance - Sugiono, Sugiono; Ihamuddin, Ilhamuddin; Rahmawan, Arief (Indonesian Journal of Disability Studies, 2014)
Inclusive education for young disabled people is a trends, issues and big challenges. Young disabled people have fewer chances to get a properly job as they are more likely to drop out after the first year and to have erratic and longer pathways within the University education. Hence, The purpose of the paper is to classify and to investigate disable students based on histories background and based on studying performance. The research was begun with literature reviews and then concentrated on the early survey (questionnaire) of the student histories. The information was classified and was analyzed to describe the correlation for all factors which is configured in graphs. The output of the paper is the summary of the sensitive trend for each factor according to disable student performance.